Study on the Disaster Risk Assessment Considering Damage Status of Human Disasters and Social Disasters in South Korea - seok Song, Young; Sup Lee, Hee; Jong Park, Moo (International Journal of Engineering and Technology, 2019)
With the effects of recent climate change, not only natural disasters such as typhoons, Heavy Rainfall and droughts, but also social disasters such as fires, collapse and infectious diseases are causing large-scale damage. The occurrence of such disasters affects various fields such as human life, social infrastructure, and economy, and research for disaster management is being carried out in various fields. In this study, disaster risk assessments by local governments were conducted for human and social disasters in Korea from 2006 to 2015. The disaster risk assessment was calculated on the average of four factors, listing the ranking of human losses, damage costs by natural disasters and social disasters. The damage status by disaster type was calculated as the risk and the overall disaster risk was evaluated. Disaster risk groups by local governments were analyzed as high risk group, middle risk group and low risk group. Gyeonggi-do, Gangwon-do, Jeollanam-do, Gyeongsangbuk-do and Gyeongsangnum-do were selected as dangerous local governments in the disaster. Other metropolitan cities and provinces were divided into middle risk group and low risk group. The results of this study are expected to be applicable to policies such as disaster management, reduction facilities and disaster related budget by assessing the disaster risk of each local government in the Republic of KoreaÂ Â